IMPLEMENTASI MODEL KOOPERATIF TEAMS GAMES TOURNAMENT PADA PEMBELAJARAN SOSIOLOGI UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK KELAS XII - Lisa Ranti Mardiyanti; Imran Imran; Iwan Ramadhan; Tri Wijaya (LPPM Universitas Muhammadiyah Muara Bungo, 2023)
The purpose of this study was to see whether students learn better by using Classroom Action Research consisting of two cycles using the Kahoot-based teams' games tournament cooperative learning model with action research steps starting from planning, implementation, and evaluation. The research involved all students of class XII Sociology TL 8 at SMA Negeri 1 Pontianak, totaling 36 people. Using interactive learning media and models is one way to improve student learning outcomes. The results showed that the learning outcomes of XII Sociology TL 8 students could be improved by implementing the Kahoot-based tournament game team cooperative learning model. The results show that by implementing the Kahoot media-based TGT learning model, students' learning outcomes have increased. In cycles 1 and 2 there was an increase in the class average of 82.5 to 85.2. In learning outcomes, there was an increase of 63% to 81%. Thus there was a significant change after using the TGT learning model.